MiR-424-5p reduces 5-fluorouracil resistance possibly by inhibiting Src/focal adhesion kinase signalling-mediated epithelial–mesenchymal transition in colon cancer cells. (13th March 2021) - Liu, Youqiang; Wang, Guiying; Li, Yong; Zhao, Qun; Fan, Liqiao; Tan, Bibo; Li, Baokun; Yu, Bin; Xi, Jinchuan
Abstract: Objectives: miR-424-5p negatively regulates various malignant biological behaviours in tumour cells. We explored the relationship between miR-424-5p and 5-fluorouracil resistance in colon cancer cells. Methods: We developed 5-fluorouracil-resistant HT-29 cells and detected miR-424-5p expression using real-time fluorescence quantitative PCR. Cell viability was assessed using Cell Counting Kit-8 (CCK-8) assay. Immunofluorescence and western blotting were performed to determine protein levels. Apoptosis was detected by Annexin V-FITC/PI staining. Key findings: miR-424-5p was downregulated in 5-fluorouracil-resistant HT-29 cells. A miR-424-5p mimic enhanced the sensitivity of the resistant cells to 5-fluorouracil, whereas a miR-424-5p inhibitor promoted 5-fluorouracil resistance in HT-29 cells. Furthermore, the miR-424-5p mimic downregulated vimentin and upregulated E-cadherin in 5-fluorouracil-resistant HT-29 cells, whereas the miR-424-5p inhibitor exhibited opposite effects. The miR-424-5p inhibitor significantly inhibited 5-fluorouracil-induced HT-29 cell apoptosis and Src and focal adhesion kinase phosphorylation, whereas the miR-424-5p mimic showed opposite effects. Pretreatment with Src inhibitor 1 or focal adhesion kinase inhibitor 2 blocked the increase in Src and focal adhesion kinase phosphorylation and vimentin expression level and the decrease in E-cadherin expression level in miR-424-5p inhibitor-exposed HT-29 cells. Conclusions: miR-424-5p suppressed epithelial–mesenchymal transition by inhibiting the Src/focal adhesion kinase signalling pathway to reduce 5-fluorouracil resistance in colon cancer cells.